Odpowiedź :
8⁻³×(8⁻³)²= 8⁻³×8 do minus 6 potegi =8 do minus 9 potegi
(9³×9²)⁻³÷(9⁴×6⁻²)⁻³=(9 do minus 9 potegi x 9do minus 6 potegi) : (9do minus 12 potegi x 6do plus 6 potegi)
9⁻³×9³= 9do minus 9 potegi
[68-(10-4)×8]×(-2)=[68-(6)x8]x(-2)= [68 +48]x(-2)= 116x2= 232
(9³×9²)⁻³÷(9⁴×6⁻²)⁻³=(9 do minus 9 potegi x 9do minus 6 potegi) : (9do minus 12 potegi x 6do plus 6 potegi)
9⁻³×9³= 9do minus 9 potegi
[68-(10-4)×8]×(-2)=[68-(6)x8]x(-2)= [68 +48]x(-2)= 116x2= 232
8⁻³×(8⁻³)²= 8⁻³ *8⁻⁶ = 8⁻⁺
(9³×9²)⁻³÷(9⁴×6⁻²)⁻³ = (9⁵ )⁻³: (9⁻¹²*6⁶) = 9⁻¹⁵ :9⁻¹²:6⁶ = 9⁻³:6⁶
9⁻³×9³ = 9° =1
[68-(10-4)×8]×(-2)= [68-(6) *8]*(-2) = [68 -48] *(-2) = 20*(-2) = -40
(9³×9²)⁻³÷(9⁴×6⁻²)⁻³ = (9⁵ )⁻³: (9⁻¹²*6⁶) = 9⁻¹⁵ :9⁻¹²:6⁶ = 9⁻³:6⁶
9⁻³×9³ = 9° =1
[68-(10-4)×8]×(-2)= [68-(6) *8]*(-2) = [68 -48] *(-2) = 20*(-2) = -40